Analysis of electrocardiograms in individuals with CDKL5 deficiency disorder. Issue 1 (13th November 2022) - Stansauk, Jessica; Fidell, Andrea; Benke, Tim; Schaffer, Michael; Demarest, Scott T.
Abstract: CDKL5 deficiency disorder (CDD) is an epileptic encephalopathy associated with medically refractory epilepsy. We sought to determine whether prolonged corrected QT interval (QTc) or other cardiac conduction abnormalities were seen in CDD in a clinical cohort. A cohort of individuals with CDD was evaluated in the Children's Hospital Colorado's International Foundation for CDKL5 Research designated Center of Excellence clinic with routine electrocardiograms obtained as part of routine clinical care. Retrospective review of electrocardiograms was completed. ECGs from 44 individuals (7 male, 37 female, age range 0–34.5 years) with pathogenic mutations and findings consistent with CDD were evaluated. Multiple ECGs were available from the 44 individuals obtained from 1996 to 2020. Prolonged QTc was found in two individuals (4.5%) and either resolved or was not confirmed on Holter monitor; no additional interventions were performed. A total of 11 individuals had echocardiograms for a variety of indications including unexplained tachycardia and ECG abnormalities; all were normal. Two individuals in the cohort died during the study with no abnormal findings on ECG. The incidence of prolonged QTc or other significant actionable cardiac abnormalities was rare in a cohort of individuals with CDD though was higher than the prevalence seen within the general population. Further studies in a larger, confirmatory cohort over a longer period are needed.